Temporal summation does not predict the acupuncture response in patients with chronic non-specific low back pain - Baeumler, Petra; Schäfer, Margherita; Möhring, Luise; Irnich, Dominik (Frontiers in Neurology, 2024)
Introduction Previously, we had observed that immediate pain reduction after one acupuncture treatment was associated with high temporal summation of pain (TS) at a pain free control site and younger age in a mixed population of chronic pain patients. The aim of the present study was to verify these results in chronic non-specific low back pain (LBP) and to collect pilot data on the association between TS and the response to an acupuncture series. Methods TS at a pain free control site (back of dominant hand) and at the pain site was quantified by the pin-prick induced wind-up ratio (WUR) in 60 LBP patients aged 50 years or younger. Response to one acupuncture treatment was assessed by change in pain intensity and pressure pain threshold (PPT) at the pain site. The primary hypothesis was that a high TS (WUR > 2.5) would be associated with a clinically relevant reduction in pain intensity of at least 30%. In study part two, 26 patients received nine additional treatments. Response to the acupuncture series was assessed by the pain intensity during the last week, the PPT and the Hannover functional ability questionnaire (FFbH-R). Results An immediate reduction in pain intensity of at least 30% was frequent irrespective of TS at the control site (low vs. high TS 58% vs. 72%, p = 0.266). High TS at the pain site was also not significantly associated with a clinically relevant immediate reduction in pain intensity (low vs. high TS 46% vs. 73%, p = 0.064). The PPT was not changed after one acupuncture treatment. Study part two did not reveal a consistent association between TS at the control site and any of the outcome measures but also a trend toward a higher chance for a clinically relevant response along with low TS at the pain site. Conclusion Our results do not suggest an important role of TS for predicting a clinically important acupuncture effect or the response to a series of 10 acupuncture treatments in patients with chronic non-specific LBP. Overall high response rates imply that acupuncture is a suitable treatment option for LBP patients irrespective of their TS.